Customer Order Scheduling in a Mobile 3D Printing Factory. Issue 10 (2022) - Alarcon-Gerbier, Eduardo; Zipfel, Benedikt; Buscher, Udo
Abstract: The problem addressed in this article is motivated by the development of small-scale, mobile factories equipped with 3D printing technologies. As they are embedded in standard containers, it is possible to move them from one location to another to support on-site and demand-driven production. To approach this problem, we developed a mixed-integer program model which defines the location of the mobile factory and assigns customer orders to each location and build, with the objective of minimizing relocation, transport, and tardiness costs. In addition, we proposed a heuristic method which, in an iterative process, builds a feasible solution and then seeks to improve it based on certain predefined rules. Early computational tests show that our algorithm achieves competitive results and can lay the groundwork for more sophisticated algorithms and problems.